Deciphering the Binding Insights of Novel Disubstituted Anthraquinone Derivatives with G‐Quadruplex DNA to Exhibit Selective Cancer Cell Cytotoxicity. (13th October 2022) - Roy, Soma; Muniyappa, Kalappa; Bhattacharya, Santanu
Abstract: Anthraquinone‐based compounds are well‐known as duplex DNA as well as G‐quadruplex DNA binders. Implications of various anthraquinone derivatives for specific recognition of G‐quadruplex DNA over duplex DNA is a 'challenging' research work that requires adequate experience with molecular design. To address this important issue, we designed and synthesized ten new 2, 6‐disubstituted anthraquinone‐based derivatives with different functionalized piperazinyl side‐chains. Among these, particular compounds with certain distant groups have shown selective and significant binding affinities toward the c‐MYC and c‐KIT G‐quadruplex DNA over the duplex DNA, as noticed from various biophysical experiments. The structural difference of quadruplex and duplex DNA was utilized to probe these derivatives for the end‐stacking mode of binding with G‐quadruplex DNA. The ability of the ligands to halt DNA synthesis by stabilizing G‐quadruplex structures is one of the crucial points to further apply them for quadruplex‐mediated anti‐cancer therapeutics. Interestingly, these ligands trigger apoptosis to exhibit selective cytotoxicity toward cancer cells over normal cells. This was further evidenced by ligand‐induced cell cycle arrest as well as cellular apoptotic morphological changes. These blood‐compatible ligands provided detailed structure‐activity relationship approaches for the molecular design of anthraquinone‐based G‐quadruplex binders. Abstract : Anthraquinone‐based compounds are known for their ability to bind duplex and G‐quadruplex DNA. Research into how members of this compound class specifically recognize G‐quadruplex DNA over duplex DNA is an important challenge. We designed and synthesized ten new 2, 6‐disubstituted anthraquinone derivatives with various piperazinyl side chains. The structural differences between quadruplex and duplex DNA were used to probe these derivatives for the end‐stacking mode of binding with G‐quadruplex DNA. These ligands were found to trigger apoptosis, exhibiting selective cytotoxicity toward cancer cells over normal cells.